Relevance of similitude parameters for drag reduction in sport aerodynamics - D'Auteuil, A.; Larose, G. L.; Zan, S. J. (Procedia Engineering, 2010)
It is possible to improve the aerodynamics of an athlete by influencing the location at which the boundary layer transition occurs on the body. The state of the boundary layer and therefore the drag coefficient depend mainly, in the critical Reynolds number range, on the shape, the aspect ratio and the 3-dimensionality of the body, the fabric properties and the wind turbulence. When planning a wind tunnel experiment, some of these factors are sometimes neglected. In this research, it was observed that each parameter was relevant and had a relatively large impact on the drag coefficient. Wind-tunnel tests on a 1:1 scale mannequin of an elite athlete were conducted in a fully controlled environment. They allowed the proper representation of the body proportions and cross-section dimensions as well as the 3-dimensionality aspect. It was observed that the flow interaction between the limbs dictated which fabric provided the lowest drag for each part of the body for a desired range of wind speed. An inappropriate simulation of the conditions can optimise the drag reduction for an erroneously targeted Reynolds number range. The research provided a quantitative evaluation of the relevance of correctly simulating parameters for drag reduction in sport aerodynamics.